Prognostic impact of age and gender on patients with electrical storm - Weidner, Kathrin; Schupp, Tobias; Rusnak, Jonas; Müller, Julian; Taton, Gabriel; Reiser, Linda; Kern-Bollow, Armin; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Barre, Max; Große Meininghaus, Dirk; et al. (Cardiology journal, 2023)
Background: Electrical storm (ES) is a severe and life-threatening heart rhythm disorder. Age and male gender have been identified as independent risk factors for cardiovascular diseases. However, data regarding the prognostic impact of age and gender on ES patients is limited. Methods: The present study included retrospectively consecutive patients presenting with ES from 2002 to 2016. Patients 67 years old or older were compared to patients younger than 67, males were also compared to females. Receiver operating characteristic analyses were performed to find the optimum age cut-off value. The primary endpoint was all-cause mortality at 3 years. The secondary endpoints were in-hospital mortality, rehospitalization rates, ES recurrences, and major adverse cardiac events (MACE) at 3 years. Results: Eighty-seven ES patients with implantable cardioverter-defibrillators were included. Age ≥ 67 years was associated with increased all-cause mortality at 3 years (48% vs. 20%, hazard ratio = 3.046; 95% confidence interval 1.316-7.051; p = 0.008; log-rank p = 0.006). MACE, in-hospital mortality, rehospitalization rates, and ES recurrences were not affected by age. Even after multivariate adjustment, age ≥ 67 years was associated with increased long-term mortality at 3 years, besides left ventricular ejection fraction < 35%. In contrast, gender was not associated with primary and secondary endpoints. Conclusions: Patients 67 years old and older presenting with ES are associated with poor long-term prognosis. Increased long-term mortality was still evident after multivariate adjustment. In contrast, gender was not associated with primary and secondary endpoints.
Gesehen am 17.11.2023